The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1103/physrevb.85.155310
|View full text |Cite
|
Sign up to set email alerts
|

Fast preparation of a single-hole spin in an InAs/GaAs quantum dot in a Voigt-geometry magnetic field

Abstract: The preparation of a coherent heavy-hole spin via ionization of a spin-polarized electron-hole pair in an InAs/GaAs quantum dot in a Voigt geometry magnetic field is experimentally investigated. For a dot with a typical bright-exciton fine-structure splitting of 17 μeV, the fidelity of the spin preparation is limited to 0.75, with optimum preparation occurring when the effective fine structure of the bright exciton matches the in-plane hole Zeeman energy. In principle, higher fidelities can be achieved by mini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…Experimental efforts have been made to characterize the g factors (i.e., components of the g tensor) of excitons [21][22][23][24][25][26], and of individual electron and holes [27][28][29][30][31][32][33][34][35][36] confined in quantum dots. Also, electric control over g factors has been shown [25,29,33,[35][36][37]; in particular, it was found that the hole g factor is much more sensitive to an electric field than the electron g factor.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental efforts have been made to characterize the g factors (i.e., components of the g tensor) of excitons [21][22][23][24][25][26], and of individual electron and holes [27][28][29][30][31][32][33][34][35][36] confined in quantum dots. Also, electric control over g factors has been shown [25,29,33,[35][36][37]; in particular, it was found that the hole g factor is much more sensitive to an electric field than the electron g factor.…”
Section: Introductionmentioning
confidence: 99%
“…For all associated quantum protocols the high fidelity initialization of single spin states that can be generated on-demand on ultra short timescales [13][14][15] and the reliable storage of the spin state is crucial 16,17 . The initialization of single spins can either be performed by spin-pumping of a charged QD 14 or by tunneling ionization of photo-generated excitons 13,[18][19][20][21] . While spin pumping is very convenient since it requires only a single continuous wave laser, it is rather slow with reported initialization fidelities of > 90% after ∼ 1ns.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Additionally, the p-type symmetry of the valence band orbitals causes a weak hyperfine interaction with the lattice nuclei, thus giving rise to decoherence times potentially longer than those of electron spins. [5,6,7,8,9,10,11] This has enabled successful hole spin initialization [12] and coherent control [10,13]. Double quantum dots (DQDs) are a natural extension which should facilitate the use of independent optical transitions for spin preparation, manipulation and readout, [14] as well as the scalability towards multiple qubit architectures.…”
Section: Introductionmentioning
confidence: 99%